Status of research results in chemistry of biologically active substances in Benin - Alain Y Koudoro; Christian Tetede Rodrigue Konfo; Philippe Sessou; Dominique C K Sohounhloue (International Journal of Phytomedicine, 2018)
Research on biologically active chemicals extracted from medicinal plants and essential oils from aromatic plants in the West African subregion is booming. Recognition of the clinical, pharmaceutical and economic value of herbal medicines continues to grow despite the growth of the pharmaceutical industry and the continued development of new, more effective synthetic and biological medical products. On the other hand, despite the improvement in food preservation technics, food preservatives nature remains one of the most important issues for public health. Indeed, several synthetic preservatives have been banned in some countries because of their long-term adverse toxicological effects. The current trend of consumers to seek for a more natural diet has prompted the research, development and application of new natural products with antimicrobial and antioxidant activities in order to use them as alternatives to synthetic preservatives. This review aims to do an inventory of the results of research in chemistry of biologically active substances in Benin.